Al-Qur’an in The Palace of Yogyakarta: Preservation, Copying, and Dissemination of the Naskah Suci - Samsul Ariyadi; Muhammad Qudwah I’tishom Billah (ZAD Al-Mufassirin, 2026)
This article examines the preservation, copying, and dissemination of the Qur'an in the Yogyakarta Palace from the 18th century to the mid-20th century. This study adopted a historiographic approach and analyzed of primary sources in the form of Qur'an manuscripts in the palace. Through this method, this study highlights the importance of the role of the palace as a cultural and religious institution that preserves the heritage of sacred manuscripts to the next generation. Furthermore, the study examined the preservation of Qur'anic manuscripts in the Yogyakarta Palace and its role in sustaining Islamic traditions within the local community. Using primary and secondary sources, the study analyzed the historical processes through which Qur'anic teachings were transmitted, adapted, and contextualized. The findings indicate that the Palace functions not only as a site of manuscript preservation but also as an institution that facilitates the interpretation of Islamic values within a Javanese cultural framework. Its contribution extends beyond safeguarding manuscripts to include the preservation of classical texts and the support of intellectual activities related to Islamic scholarship. Furthermore, the study demonstrates that these preservation practices help maintain the continuity of Islamic teachings while enabling their relevance in changing social contexts.